2006
DOI: 10.1111/j.1756-2171.2006.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Spin-outs: knowledge diffusion through employee mobility

Abstract: In many industries, one important method of diffusion is through employee mobility: many of the entering firms are started by employees from incumbent firms using some of their former employer's technological know‐how. This article explores the effect of incorporating this mechanism in a general industry framework by allowing employees to imitate their employers' know‐how. The equilibrium is Pareto optimal because the employees “pay” for the possibility of learning their employers' know‐how. The model's implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
284
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(310 citation statements)
references
References 17 publications
9
284
0
5
Order By: Relevance
“…Other theories have attributed this to the superior learning environment for employees at better firms (cf. Franco and Filson [2006]), but our theory demonstrates this is not needed to explain the correlation. Our theory readily explains the repeated finding that organizational changes within firms tend to raise the probability of spinoffs.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Other theories have attributed this to the superior learning environment for employees at better firms (cf. Franco and Filson [2006]), but our theory demonstrates this is not needed to explain the correlation. Our theory readily explains the repeated finding that organizational changes within firms tend to raise the probability of spinoffs.…”
Section: Discussionmentioning
confidence: 94%
“…10 In disk drives, Agarwal et al [2004] found that firms with better technology had spinoffs with better technology, and firms (of all types) with better technology survived longer. However, in a direct analysis of the relationship between spinoff longevity and characteristics of parents, Franco and Filson [2006] did not find that spinoffs from parents with better technology survived longer (if anything, they survived shorter).…”
Section: Empirical Regularitiesmentioning
confidence: 99%
See 3 more Smart Citations